Application of Stress and Anxiety to Viral Epidemics-6 Items (SAVE-6) to Public Workers for Measuring Their Anxiety Response During the COVID-19 Pandemic - Park, C. Hyung Keun; Ju, Gawon; Yi, Kikyoung; Lee, Sangha; Suh, Sooyeon; Chung, Seockhoon (Frontiers in Psychiatry, 2021)
Objective: This study aimed to compare the adaptability of the adapted version of Stress and Anxiety to Viral Epidemics-9 (SAVE-9) for public workers and the SAVE-6 scale and to validate them among public workers who are on the frontline of the coronavirus disease 2019 pandemic. Methods: A total of 300 public workers responded to the anonymous online survey. Principal component analysis was conducted to explore actor structure of this scale. Confirmatory factor analysis was used to explore construct validity. Spearman correlation analysis of the scale with the Generalized Anxiety Disorder-7(GAD-7) and the Patient Health Questionnaire-9(PHQ-9) was performed to explore the convergent validity. The cut-off score in accordance with the mild degree of generalized anxiety symptoms was defined using the receiver operating characteristic (ROC) analysis. Findings: The single-structure model of each scale (the adapted version of SAVE-9 and SAVE-6) was adopted based on the results of the parallel analysis. Because SAVE-6 showed good construct validity, but the adapted version of SAVE-9 did not, we adopted to apply the SAVE-6 scale to assess the anxiety response of public workers in response to the viral epidemic. SAVE-6 showed good internal consistency(Cronbach’s alpha=0.817; McDonald’s Omega=0.818) and good convergent validity with GAD-7(rho=0.417, p<0.001) and PHQ-9(rho=0.317, p<0.001) scale scores. The appropriate cut-off score for SAVE-6 was determined to be ≥ 16. Conclusion: The SAVE-6 scale, as compared to the public workers’ version of SAVE-9, is a reliable and valid rating scale to assess the work-related stress and anxiety of public workers due to the viral epidemic.